Charge-traps, thermal stability and water-uptakes of CaSiO3/EP and SiO2/EP nanocomposites from molecular simulations and first-principles calculations - Zhang, Yanyan (2024)
Various analytical methods were employed to elucidate the effects of filling nano-calcium-silicate or nano-silica on the electronic property, water-uptake, and thermal stability of an amine-crosslinked epoxy (EP) polymer. Molecular-mixture models consisting of a nanofiller or several calcium ions and EP crosslinked macro-molecules were used to simulate local regions of nanofiller/matrix interface or ion-infiltrated matrix, calculating their density of electron-states by first-principles method to determine whether and how the nanofillers introduce charge traps into EP matrix. Calcium cations on nanofiller surface dissociate away from coordinating with silicon-oxygen tetrahedron and infiltrate into void spaces in EP matrix, leaving a larger free volume at filler/matrix interface than in matrix. Calcium cations dissolved in EP matrix are adsorbed in the low electrostatic potential region or coordinate with carbonyl groups in EP matrix and thus introduce a miniband of deep electron traps at energy levels >1 eV lower than conduction band minimum of the amine-crosslinked EP polymer. Even at room temperature, thermal vibrations can break coordinate bonds between calcium cations and silicon-oxygen framework on calcium-silicate nanofiller surface and make considerable calcium ions infiltrating void spaces within EP matrix, leading to comprehensive improvements of cohesive energy, thermal stability, and charge trapping ability in the calcium-silicate/EP nanocomposite.